2020
DOI: 10.1108/mabr-03-2020-0016
|View full text |Cite
|
Sign up to set email alerts
|

The global trends of automated container terminal: a systematic literature review

Abstract: Purpose Since the first automated container terminal (ACT) was introduced at Europe Container Terminals Delta Terminal in Port Rotterdam back in the year 1992, a lot of research had been done to improve the management of ACT. However, up until recently, the number of literature available still appeared scarce. Hence, this paper aims to review the collection of literature about ACT to generate an exhaustive summary to answer the formulated review question in this study. Design/methodology/approach Preferred r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 158 publications
0
23
0
Order By: Relevance
“…Camarero Orive et al ( 2020 ) listed 44 container terminals in the world using automated handling technology. Kon et al ( 2020 ) reported that 54 automated terminals were opened between 1993 and 2020. ITF ( 2021 ) reports 53 automated container terminals, representing around 4% of the total global container terminal capacity.…”
Section: Empirical Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Camarero Orive et al ( 2020 ) listed 44 container terminals in the world using automated handling technology. Kon et al ( 2020 ) reported that 54 automated terminals were opened between 1993 and 2020. ITF ( 2021 ) reports 53 automated container terminals, representing around 4% of the total global container terminal capacity.…”
Section: Empirical Findingsmentioning
confidence: 99%
“…In the past decade, container terminal automation has attracted much attention in business, policy, and, subsequently, academic circles (Kon et al, 2020 , Ghiara and Tei 2021 , see also Sect. 3 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Automation of container terminals is a topic that has been studied since the ECT's Delta/Sea-Land terminal started operating in the early nineties. A systematic literature review on automated container terminals recently established that approximately 200 papers discussing results from applying automated technologies in container terminals have been published [8]. These papers mostly focus on specific problems of automated equipment and optimization issues.…”
Section: Literature Overview and Research Gapmentioning
confidence: 99%
“…These papers mostly focus on specific problems of automated equipment and optimization issues. None of the research focusses on brownfield automation implementation [8].…”
Section: Literature Overview and Research Gapmentioning
confidence: 99%